Innate Immune Programing by Endotoxin and Its Pathological Consequences - Morris, Matthew C.; Gilliam, Elizabeth A.; Li, Liwu (Frontiers in Immunology, 2015)
Monocytes and macrophages play pivotal roles in inflammation and homeostasis. Recent studies suggest dynamic programming of macrophages and monocytes may give rise to distinct “memory” states. Lipopolysaccharide (LPS), a classical pattern recognition molecule, dynamically programs innate immune responses. Emerging studies have revealed complex dynamics of cellular responses to LPS, with high doses causing acute, resolving inflammation, while lower doses are associated with low-grade and chronic non-resolving inflammation. These phenomena hints at dynamic complexities of intra-cellular signaling circuits downstream of the Toll-like-receptor 4 (TLR4). In this review, we examine pathological effects of varying LPS doses with respect to the dynamics of innate immune responses and key molecular regulatory circuits responsible for these effects.